The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.13189/ujm.2018.060601
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for and Comparisons of Green Certificates within the Hotel Industry

Abstract: A blooming hotel industry has the downside of an increased negative environmental impact. At the same time, many hotel guests and employees have become conscious of eco-friendliness and green practices. In addition, 2017 was by United Nations declared as the International Year of Sustainable Tourism for Development, with the emphasis on (among other elements) resource efficiency and environmental protection. A hotel that has obtained green certificate(s) promises green services, products, and operations, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Previous research has indicated that not only sustainable practices, but also environmental green certificates are components which can develop the green image of a hotel and ultimately represent a competitive advantage for the hotel. Green certificates (e.g., the EU Ecolabel) may improve the hotel's relationships with its close stakeholders, like customers and suppliers [18], but also result in an improved corporate image and reputation among the general public [5,19]. It is also important to integrate internal stakeholders, the managers and employees, in the educational efforts to increase sustainability awareness and specific knowledge, including specific training programs about environmental protection [5,20].…”
Section: Sustainability and Hotelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has indicated that not only sustainable practices, but also environmental green certificates are components which can develop the green image of a hotel and ultimately represent a competitive advantage for the hotel. Green certificates (e.g., the EU Ecolabel) may improve the hotel's relationships with its close stakeholders, like customers and suppliers [18], but also result in an improved corporate image and reputation among the general public [5,19]. It is also important to integrate internal stakeholders, the managers and employees, in the educational efforts to increase sustainability awareness and specific knowledge, including specific training programs about environmental protection [5,20].…”
Section: Sustainability and Hotelsmentioning
confidence: 99%
“…Green certificates (e.g., the EU Ecolabel) may improve the hotel's relationships with its close stakeholders, like customers and suppliers [18], but also result in an improved corporate image and reputation among the general public [5,19]. It is also important to integrate internal stakeholders, the managers and employees, in the educational efforts to increase sustainability awareness and specific knowledge, including specific training programs about environmental protection [5,20]. Buffa et al [21] took a broader view, emphasizing that hotels' sustainability policies can contribute to destination competitiveness by building collaborative relationships with key stakeholders and actors in the local environment.…”
Section: Sustainability and Hotelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing alternate water sources, such as rainwater, surface water, and recycled water, is one example of direct conservation strategies. Examples of indirect water conservation strategies include pressure management and the use of efficient fixtures (Eskerod, P. and Duric, J., 2018). Due to the performance of the materials used to construct these structures, residents of green buildings enjoy numerous health benefits.…”
Section: Importance Of Green Certificatementioning
confidence: 99%
“…The construction industry has been recognized as an economic regulator of any nation due to its substantial contribution to the nation's Gross Domestic Product and its economic multiplier effect. (Giang, D. T. H. andSui Pheng, L., 2011, Eskerod, P. andDuric, J., 2018). Even though construction is important to the national economy, it has a negative influence on the natural environment.…”
Section: Introductionmentioning
confidence: 99%